Fungi from cycas and pandanus leaves in Taklong Island, Guimaras. - Lim, Mary Ellen (1998.)
Fungi are one of the most important component of our ecosystem. They have a wide range of functions to other animals, man and to the environment. However, there has been a relatively few biodiversity studies conducted in their occurrence. Few known studies have been conducted on Pandanus in the tropics., This study was undertaken 1) to determine the occurrence (to identify, classify and describe) of fungal species on Cycas and Pandanus on selected sites in Taklong Island, Guimaras; and 2) to measure the biodiversity of fungi on Cycas and Pandanus during October and November 1997 collections. Two collections were made from selected sites at Taklong Island, Guimaras where abundant species of Cycas and Pandanus are found. Antibiotic parameters (air temperature and humidity) of the study areas were noted and only dead and decaying were collected. The isolation of fungal species was done at the UPV Biological Sciences laboratory Miag-ao. For the isolation of the fungal species a modified sterilized agar disc culture method was adopted. The examination and identification of fungi were done with the aid of Keys for Identification. The species collected were classified according to their frequency of occurrence of each species (very frequent:>30, frequent: 10-29, infrequent:<10). A total of 16 fungal were isolated from both Cycas and Pandanus. Two species belonged to the Division Ascomycota and 14 species belonged to the Division Deuteromycota. There were six unidentified species thus assigned as species E, species F, species H, species L, species N, and species R. The ascomycetes were Mycosphaerella sp. and species L. The deuteromycetes included Aspergillus sp., Cladosporium sp., Curvularia sp., Drechsclera sp., species E, species F, Fusarium sp., species H, Mycelia sterilia N, species R, Rhizopus sp., Scytilidium cf. sp., and Shearia cf. sp. There were three frequent species recorded among the two hosts and between collections. These are Asperigillus sp. (16.80). There were 11 fungal species isolated from Cycas and 13 species were found to inhabit Pandanus. Factor such as nature of the substrate and the site (open area for wind and tide actions), specificity on the host and action on the host may influence the presence of fungi on these hosts.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Fungi -- Taklong Island, Guimaras